Factors influencing undernutrition among children under 5 years from cocoa-growing communities in Bougainville - Kirsten Black; Justin Beardsley; Jessica Hall; Merrilyn Walton; Floris Van Ogtrop; David Guest (BMJ Global Health)
Half the children under the age of 5 years in Papua New Guinea (PNG) are undernourished, more than double the global average with rural areas disproportionately affected. This study examines factors associated with stunting, wasting and underweight in cocoa growers’ children (<5 years) in the Autonomous Region of Bougainville (ARoB), using data from a comprehensive 2017 cross-sectional livelihoods survey. Sixteen independent predictors for stunting, wasting and underweight were selected based on the UNICEF Conceptual Framework of Determinants of Undernutrition. We used multilevel logistic mixed regression models to measure the association of the explanatory variables with stunting, wasting and underweight. At the household level, the adjusted OR (aOR) of stunting (aOR=1.71,95% CI 1.14 to 2.55) and underweight (aOR=2.11, 95% CI 1.16 to 3.82) increased significantly among children from households with unimproved toilet facilities. The aOR for underweight also increased among children from households without access to clean drinking water (aOR=1.97, 95% CI 1.19 to 3.29). Short maternal stature was significantly associated with child stunting, the odds increased as maternal height decreased (from 150 to <155 cm, aOR=1.52, 95% CI 1.02 to 2.26) (<150 cm, aOR=2.37, 95% CI 1.29 to 4.35). At the individual level, the odds of a child being underweight increased with birth order (second born, aOR=1.92, 95% CI 1.09 to 3.36; third born, aOR=6.77, 95% CI 2.00 to 22.82). Compared with children less than 6 months, children aged 6–23 months and 24–59 months had a higher odds of being stunted (aOR=3.27, 95% CI 1.57 to 6.78 and aOR=2.82, 95% CI 1.40 to 5.67) and underweight (aOR=4.83, 95% CI 1.36 to 17.24 and aOR=4.59, 95% CI 1.29 to 16.26). No variables were found to be significant for wasting. Interventions that simultaneously target key life stages for women and children and the underlying social and environmental determinants are required for sustained improvements to undernutrition.